Bilderstreit; Widerspruch, Einheit und fragment in der Kunst seit 1960. - Gohr, S.; Gachnang, J. (Köln : DuMont Buchverlag, 1989)
Altenbourg, Gerhard ; Andre, Carl ; Anselmo, Giovanni ; Anzinger, Siegfried ; Artschwager, Richard ; Baldessari, John ; Balthus ; Baselitz, Georg ; Baumgarten, Lothar ; Becher, Bernd & Hilla ; Bess, Forrest ; Beuys, Joseph ; Bickerton, Ashley ; Bourgeois, Louise ; Braque, Georges ; Brecht, George ; Broodthaers, Marcel ; Brouwn, Stanley ; Brus, Günter ; Buren, Daniel ; Byars, James Lee ; Chaissac, Gaston ; Chamberlain, John ; De Chirico, Giorgio ; Clemente, Francesco ; Copley, William ; Dahn, Walter ; Daniels, René ; Darboven, Hanne ; Derain, André ; Dibbets, Jan ; Dubuffet, Jean ; Duchamp, Marcel ; Dumas, Marlene ; Ernst, Max ; Fabro, Luciano ; Fautrier, Jean ; Federle, Helmut ; Filliou, Robert ; Fischl, Eric ; Riverhead (New York) ; Fontana, Lucio ; Förg, Gunther ; Freundlich, Otto ; Giacometti, Alberto ; Gilbert & George ; van Golden, Daan ; Gruber, Francis ; Guston, Philip ; Hains, Raymond ; Herold, Georg ; Hesse, Eva ; Höckelmann, Antonius ; Hodgkin, Howard ; Immendorff, Jörg ; Jensen, Alfred ; Johns, Jasper ; Jorn, Asger ; Judd, Donald ; Kasseböhmer, Axel ; Kawara, On ; Kelly, Ellsworth ; Kiefer, Anselm ; Kiesler, Friedrich ; Kirkeby, Per ; Klein, Yves ; Klossowski, Pierre ; Knoebel, Imi ; Kounellis, Jannis ; Kruger, Barbara ; Leroy, Eugène ; Levine, Sherrie ; LeWitt, Sol ; Lichtenstein, Roy ; Long, Richard ; Lüpertz, Markus ; Magritte, René ; Malevich, Kasimir ; Man Ray ; Manzoni, Piero ; Marden, Brice ; De Maria, Nicola ; Martin, Agnes ; McCollum, Allan ; Merz, Mario ; Merz, Marisa ; Mondriaan, Piet ; Mortensen, Richard ; Mucha, Reinhard ; Munch, Edvard ; Nauman, Bruce ; Nay, Ernst Wilhelm ; Newman, Barnett ; Nitsch, Hermann ; Oehlen, Albert ; Oppenheim, Meret ; Palermo, Blinky ; Paolini, Giulio ; Pascali, Pino ; Penck, A.R. ; etc.
boek